Utilization of Human Induced Pluripotent Stem Cells for Cardiac Repair - Fan, Chengming; Zhang, Eric; Joshi, Jyotsna; Yang, Jinfu; Zhang, Jianyi; Zhu, Wuqiang (Frontiers in Cell and Developmental Biology, 2020)
Paracrine effect is an important mechanism for stem cell-based therapy. Extracellular microvesicles, such as exosomes, are nano-sized vesicles of endosomal origin and have been demonstrated to be a major contributor for stem cell-mediated paracrine effects. Specifically, exosomes from implanted stem cells have been shown to regulate cell apoptosis, proliferation, angiogenesis and fibrosis in the recipient heart. Exosomes also play important role in the intercellular communication between donor cells and the host myocardium. Human induced pluripotent stem cell (hiPSC) is a promising cell source for autologous cell therapy in regenerative medicine. Here, we review the recent advances in the field of cardiac repair with exosomes derived from stem cells with special emphasis with hiPSCs.